Building an Informatics-Savvy Health Department II. Issue 1 (January 2015) - LaVenture, Martin; Brand, Bill; Ross, David A.; Baker, Edward L.; Baker, Edward L.
<x xml:space="preserve">Abstract</x> In this article, the authors build on their previous discussion of the vision and core strategies for building an informatics-savvy health department to describe the operational and tactical details related to reaching this goal.